Clinical and laboratory characteristics of influenza infection in hospitalized adult patients during the 2018-2019 epidemic season - L. V. Voloshchuk (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
Despite the success in prevention and therapy, influenza remains a mass disease with mortality rate up to 0.01—0.2% worldwide.Purpose. Conducting clinical and laboratory analysis of influenza infection cases and evaluating their etiological significance in adult hospitalized patients during 2018—2019 epidemic season. Materials and methods. There were analyzed 569 case histories of patients hospitalized at the Clinical Infectious Diseases Hospital named after S.P. Botkin. Patients were examined by PCR that resulted in verified influenza virus in 260 cases. Nasopharyngeal swabs collected from 36 patients were examined by virological method on MDCK cell culture. 24 influenza virus strains were isolated and identified.Results. The study allowed to identify a viral landscape represented by influenza viruses A and B found in 98.5% and 1.5% cases, respectively. Influenza viruses isolated on cell culture in 50% of cases were identified. Among the influenza viruses isolated on cell culture there were identified serotype A influenza viruses (H1N1) closely related to the pandemic influenza A (H1N1)pdm09. Some isolates (41.7%) belonged to serotype A (H3N2), which were related to strain A/Singapore/16-0019/16. Influenza B virus strain of the Victoria lineage isolated from a hospitalized patient possessed a triple deletion in hemagglutinin gene, which antigenic properties substantially differed from those of the influenza virus strain being included into current influenza vaccines. Upon admission, the condition of most patients was estimated as moderate (males — 48.7%, females — 51.3%). The median patient age was 35 years old, with comorbidities being registered in 50% cases. The clinical picture for 2018—2019 seasonal influenza displayed no distinctive features as compared to previous epidemic seasons. The duration of intoxication and catarrhal syndrome was 4.3±0.13 and 6.9±0.29 days, respectively, with median body temperature ranging within 39.2±0.06°С. All patients received standard pathogenetic therapy. Complications were noted in 86.7% cases such as pneumonia — 11.1%, sinusitis — 6.9%, bronchitis — 56.9%. The bed day length was 5.93±0.29, no lethal outcomes were recorded.Conclusion. It was found that influenza A viruses were dominant in patients observed comprising up to 98.5% cases, whereas influenza viruses B were found in as few as 1.5% patients. The clinical picture was characterized by severe intoxication and catarrhal syndrome, being frequently associated with complications.